Trick or deceit - Freydont, Shelley (Freydont, Shelley. Celebration Bay mystery., 2015)
"This October in Celebration Bay, you cant swing a black cat without hitting a haunted house. There are three finalists in the contest for the town's official Haunted House, and ten thousand dollars will go to the winner, with the rest of the proceeds funding a new community center. Event coordinator Liv Montgomery has invited her friend Jonathan Preston, the debonair director of development for a philanthropic organization, to visit town, hoping he will also award a grant to the center. After the Museum of Yankee Horrors wins first place, the transformed Victorian boardinghouse is vandalized. Among scattered mannequins of Hester Prynne, Lizzie Borden, and the Headless Horseman, a real dead body is found--one of the contest judges. Now in addition to playing host to Jon, Liv has to play detective and coordinate the clues to unmask a self-appointed judge, jury, and executioner"--Page [4] of cover.